Pengawasan Pemberian Izin Tempat Penjualan Minuman Beralkohol di Kota Palangka Raya - Mambang Mambang; Muhammad Afriyanor (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2017)
This study aims to explain and describe the Supervision of Granting Permits for Selling Alcoholic Beverages. The research method used is a qualitative research method, using data collection techniques through observation, interviews, and documentation. Data analysis uses qualitative data analysis, namely data reduction, data presentation, and withdrawal of income. The data sources in this study are the Employees of the Department of Industry and Trade of Palangka Raya City, as well as the community with the owner of the Special Signed Shop / Alcoholic Beverage Shop. Based on the results of the study showed that the Supervision of Granting Permits for the Sale of Alcoholic Beverages is still not carried out optimally, because of the four indicators of policy implementation, only one that works well is the indicator of Support. The other three indicators (Information, Fill in the Nutrition, and Potential Distribution) have not run optimally. It is recommended that the Perangkautrian and Trade Office of the City of Palangka Raya not violate the existing rules, so the Special Signed Shop that violates the rules adjacent to places of worship, schools, and hospitals so that no permission is granted.